PENGARUH ORIENTASI ETIKA TERHADAP MANAJEMEN LABA - Kamaruddin DP (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
The purpose of this study was to analyze the influence of ethical orientation on the perception of unethical accountants about earnings management practices. Data analysis methods used in the study is descriptive statistics, testing the quality of the data, the classical assumption, and hypothesis testing. The results of the research is ethical orientation significant positive effect on the perception of unethical accountants about earnings management practices. This illustrates that the increase in ethical orientation on accountants will have an impact on professional decision making that will improve the perception of unethical accountants about earnings management practices.